The DNA damage checkpoint and the spindle position checkpoint: guardians of meiotic commitment - Ballew, Olivia (Curr Genet, 2019)
Exogenous signals induce cells to enter the specialized cell division process of meiosis, which produces haploid gametes from diploid progenitor cells. Once cells initiate the meiotic divisions, it is imperative that they complete meiosis. Inappropriate exit from meiosis and entrance into mitosis can create polyploid cells and can lead to germline tumors. S. cerevisiae cells enter meiosis when starved of nutrients but can return to mitosis if provided nutrient-rich medium before a defined commitment point. Once past the meiotic commitment point in prometaphase I, cells stay committed to meiosis even in the presence of a mitosis-inducing signal. Recent research investigated the maintenance of meiotic commitment in budding yeast and found that two checkpoints that do not normally function in meiosis I, the DNA damage checkpoint and the spindle position checkpoint, have crucial functions in maintaining meiotic commitment. Here, we review these findings and discuss how the mitosis-inducing signal of nutrient-rich medium could activate these two checkpoints in meiosis to prevent inappropriate meiotic exit.